Violence Gender Violence In Virtual Sexual Harassment On Social Media Telegram: Gender Violence In Virtual Sexual Harassment On Social Media Telegram - Melpin Simaremare Simaremare; Farid Pribadi (Fakultas Ilmu Sosial dan Hukum, Universitas Negeri Surabaya, 2022)
Abstract The continuous occurrence of revolution in society will certainly lead to changes and developments in the community. Information and communication factors are one of the drivers of the revolution in society. The more information and communication activities carried out by the community will certainly lead to the development of the community. The development of information and communication in the community does not only have a positive impact on the development of the community's social system, but it turns out that the development of this information and communication can become a tool to take negative actions such as committing acts of gender-based violence. Social media is a media space that is accessed and used to get information and communicate easily by reaching other people passively. But unfortunately, social media is also used as one of the tools used to carry out acts of gender-based violence that are more directed to acts of sexual harassment in virtual form with social media. One of the social media used as a tool to commit sexual harassment is telegram which should be used as a tool to communicate. This research was conducted to find out the factors and reasons that encourage perpetrators to commit acts of virtual sexual harassment and with this research it is hoped that it can increase public awareness and understanding of gender equality so that there are no many acts of gender-based sexual harassment. Keywords: Social Media, Violence, Gender, Information, Communication